An experimental investigation of hub drag characteristics on coaxial rotor aircraft - Min Tang; MingQi Huang; YongDong Yang; Dong Li (My University, 2018)
A full-scale wind tunnel tests have been conducted to research the hub drag characteristics of combine coaxial rotor aircraft and better understand the aerodynamic interaction between hub and fairings. A hub and fairing drag test was conducted to obtain quantitative drag measurements on multiple fairing geometries, and to get insight into the effect of rotation and the presence of blade stub. There were four interchangeable mid-shaft fairings designed, i.e., optimized fairings F1, F2 based on airfoil and optimized fairing F3, plus a bare shaft(S) for reference. The effect on the hub drag of varying angle of attack, Mach number were investigated. Principal results were that the Mach number had a greater influence on the drag of hub, and the best fairing configuration reduced the drag of coaxial rotor hub by 37%. The test also provided validation data for computational fluid dynamics (CFD), and aerodynamic characteristics for design.